Fetal growth and psychiatric and socioeconomic problems: population-based sibling comparison. (November 2014) - Class, Quetzal A.; Rickert, Martin E.; Larsson, Henrik; Lichtenstein, Paul; D'Onofrio, Brian M.
Abstract : Background: It is unclear whether associations between fetal growth and psychiatric and socioeconomic problems are consistent with causal mechanisms. Aims: To estimate the extent to which associations are a result of unmeasured confounding factors using a sibling-comparison approach. Method: We predicted outcomes from continuously measured birth weight in a Swedish population cohort ( n = 3 291 773), while controlling for measured and unmeasured confounding. Results: In the population, lower birth weight (⩽2500 g) increased the risk of all outcomes. Sibling-comparison models indicated that lower birth weight independently predicted increased risk for autism spectrum disorder (hazard ratio for low birth weight = 2.44, 95% CI 1.99–2.97) and attention-deficit hyperactivity disorder. Although attenuated, associations remained for psychotic or bipolar disorder and educational problems. Associations with suicide attempt, substance use problems and social welfare receipt, however, were fully attenuated in sibling comparisons. Conclusions: Results suggest that fetal growth, and factors that influence it, contribute to psychiatric and socioeconomic problems.